Pengenalan Warna Dan Bentuk Untuk Anak Usia 4-6 Tahun Berbasis Augmented Reality - Maria Ulfah; Emmy Wahyuningtyas; Beny Y.V. Nasution (Informatics Engineering Department-UWKS, 2016)
The introduction of color and shape for early childhood are still using face-to-face or a book, so that children who want to learn to feel tired and lack of instructional media about the introduction of color and shape-based 3D. Learning by this method can lead to boredom for early childhood. Therefore, given a solution by creating instructional media introduction of color and shapes for children ages 4-6 years based AR (augmented reality). It can be said that the application has been successful with the success rate of the percentage rate at which the trial introduction of color in terms of indicators of children who can recognize objects that is 70%. To test the introduction of forms in terms of indicators of children who can recognize objects that is 66.67%. To test the introduction of objects that resemble the shape of a child in terms of indicators that can recognize objects, namely 87.3%. So that the application is eligible to serve as a medium of learning.